Implementasi Kegiatan Khitobah Untuk Menumbuhkan Karakter Percaya Diri Santri di Pondok Pesantren Nawwir Quluubana Wonosobo Tahun 2024 - Botok Rahayu; Ngarifn Shidiq; Vava Imam Agus Faisal (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Self-confidence is needed by students in everyday life. The community considers santri to be versatile in everything, in this case the Nawwir Quluubana Islamic Boarding School organizes activities to equip santri skills for when they enter the community. The researcher in this case aims to find out about how khitobah activities are able to foster the confident character of students at the Nawwir Quluubana Wonosobo Islamic Boarding School, then to know what are the supporting and inhibiting factors of khiotbah activities in fostering the confident character of students at the Nawwir Quluubana Islamic Boarding School. A qualitative research approach is used with the type of field research then produces descriptive data. The data was collected by direct observation, in-depth interviews and documentation. The results show that khitobah activities affect students' self-confidence. The hope is to develop santri self-confidence, train santri to be more courageous in public, and be able to provide the benefits of their knowledge in the community. The supporting factors are the encouragement and motivation of caregivers and administrators, the factor of careful preparation of students, the factor of adequate facilities and the increasing knowledge of students who previously did not know so they know. The inhibiting factors are the lack of interest of the students in improving their public speaking skills, the lack of knowledge and experience of the students and the less than optimal students in using the facilities.